THE RELEVANCE OF THE HADITH OF SIMPLICITY TO THE LIFESTYLE OF PRESIDENT JOKO WIDODO - Azzahra, Fulaifah; Friyadi, Arif (RIWAYAH, 2024)
This paper seeks to find out about President Jokowi’s lifestyle that can implement the simplicity of the Prophet Muhammad based on the hadiths of zuhd of the Prophet. The power and authority of positions in government are synonymous with luxury and hedonistic lifestyles. The hedonistic nature of an official often leads to corruption. This is due to dissatisfaction with the salary and benefits he gets from the state. President Jokowi (2014-2024) lives very simply like the life of ordinary people. This is in accordance with the reflection of the Prophet’s life as a counter to the hedonism of a leader. The President described the life of the apostle who was so simple starting from the way he dressed, sandals, hairstyle, food, and drinks. This paper uses a qualitative descriptive method with a library research approach. In this case the author collects data from various existing reading sources both through print and online media. From here the author finds that the simple lifestyle of President Jokowi through the way he dresses, the food he eats, and the way he uses social media is a reflection of the apostle himself. The author also presents hadiths that are in accordance with the description of the Prophet’s simple life and then interconnects the sunnah with Joko Widodo’s life. Through this paper, it is hoped that leaders will realize their responsibility as leaders among the people so that they will not enrich themselves because of their greed for material possessions.[Tulisan ini berupaya mencari tahu tentang pola hidup Presiden Jokowi yang dapat mengimplementasikan kesederhanaan Nabi Muhammad berdasarkan hadis-hadis zuhud. Kekuasaan dan wewenang jabatan dalam pemerintahaan sudah identik dengan yang namanya bermewah-mewahan serta gaya hidup hedonis. Sifat hedon seorang pejabat sering menarik kepada tindak pidana korupsi. Hal ini disebabkan ketidakpuasan dengan gaji dan tunjangan yang dia dapat dari negara. Presiden Jokowi (2014-2024) hidup dengan sangat sederhana layaknya kehidupan rakyat biasa. Hal ini sesuai dengan cerminan hidup The Prophet sebagai perlawanan sikap hedonisme seorang pemimpin. Presiden menggambarkan kehidupan Rasul yang begitu sederhana mulai dari cara berpakaian, sandal, gaya rambut, makanan, dan minuman. Tulisan ini menggunakan metode deskriptif kualitatif dengan pendekatan library research. Dalam hal ini penulis mengumpulkan data dari berbagai sumber bacaan yang ada baik melalui media cetak maupun online. Dari sini penulis menemukan gaya hidup sederhana seorang Presiden Jokowi melalui cara berpakaian, makanan yang dimakan, dan cara menggunakan medsos merupakan cerminan dari diri Rasul. Penulis juga memaparkan hadis-hadis yang sesuai dengan gambaran kehidupan sederhana The Prophet yang kemudian menginterkoneksikan antara sunnah dengan kehidupan Joko Widodo. Melalui tulisan ini diharapkan para pemimpin sadar akan tanggung jawab sebagai pemimpin di antara umat sehingga tidak akan memperkaya diri karena sifat tamak kepada harta benda.]